Productivity Estimations for the Economy Sector - Kaminskienė, Bronislava; Misiūnas, Algimantas (Ekonomika, 2000)
The main gaol of this work is estimating of productivity in Lithuania. Productivity is defined as the ratio of output to one or more inputs. Labor and multifactor productivity arc estimated by all kind of activities. Labor productivity at basic prices as estimated as well as index.